Building a strategy based on the Sternberg model and measuring its impact on the achievement of art education students in the subject of teaching methods and developing their mental alertness. (Journal of the College of Basic Education, 2026)
The aim of the current research is to:Building a strategy teaching according to Sternberg's model For an art education subject.Study Impact of strategy in the achievement of students of the Department of Art Education in the subject of teaching methods.To achieve the research objectives, the researcher formulated the following hypotheses: Hypothesis (1): There are no differences Statistical significance between the average scores of the experimental group that studied according to the strategy New and average grades of the control group that studied according to the usual method in Vigilance level Mental later.Hypothesis (2): There are no statistically significant differences between the average scores of the experimental group, pre- and post- At the level of mindfulness.Hypothesis (3): There are no statistically significant differences between the average scores of the experimental group that was studied according to the strategy The new and average scores of the control group that studied according to the usual method in the achievement test later.The current research included four chapters The first chapter included a general framework for the research, starting with the research problem, which the researcher arrived at through: Teaching it to students Department of Art Education: Some students lack To the ability to pay attention or focus on their work. They are characterized by a weak ability to integrate into more than one work, and they perform their work without awareness on their part. They are characterized by mental distraction inside the classroom and their lack of use of their previous experiences in facing new problems.Accordingly, the research problem was represented in: In the following question: (What is the impact of a strategy based on the Sternberg model on the achievement of students in the Art Education Department in the subject of teaching methods?) As well as the importance of research.The second chapter dealt with a theoretical framework for the research and previous studies, then the third chapter dealt with the research procedures represented by the research community consisting of the students of the Art Education Department, numbering (851), while the research sample was represented by the third stage students, Sabahi, numbering (64) male and female students.The study was applied to the research sample after the researcher prepared the achievement test. To show the research results, the researcher used the statistical bag (SPSS)While the fourth chapter included presenting and interpreting the results reached by the researcher using the statistical bag (SPSS) in the previous chapter it was as follows:There are no statistically significant differences between the averages of the experimental and control groups with respect to the pre-achievement test variable, as the calculated T value amounted to (0.599) versus the tabular (2.00).There are statistically significant differences between the averages of the experimental and control groups with respect to the achievement test variable later, as the calculated T value reached 6,713) versus the tabular (2.00) and the difference is in favor of the experimental group.There are statistically significant differences between the averages of the pre- and post-tests of the experimental group with respect to the achievement variable, where the T value reached 5,012) versus the tabular (2,00) in favor of the post-test.The researcher reached a number of conclusions, the most prominent of which were:The research results demonstrated that the educational strategy based on the Sternberg model is feasible for construction and application in the subject of teaching methods for students of the Art Education Department. It was prepared in an organized, scientific manner that takes into account the different thinking styles of students. The results showed no statistically significant differences between the experimental and control groups in the pre-achievement test, which indicates the equivalence of the two groups before applying the experiment, and enhances the credibility of subsequent results.In continuation of the current research, the researcher recommended: Adopting the new educational strategy within the plans to develop the teaching of teaching methods in the Department of Art Education and other departments in the College of Basic Education within the teaching methods course, in line with the orientations of the Ministry of Higher Education and Scientific Research towards improving the quality of university education, as well as integrating modern thinking strategies into teaching preparation and training programs in a way that contributes to raising their professional efficiency, and is consistent with the Ministry's policies to modernize university teaching methods.